ANALISIS FAKTOR-FAKTOR BAURAN PEMASARAN YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN SATE LILIT IKAN PADA WARUNG LESEHAN MERTA SARI PESINGGAHAN, KLUNGKUNG - Purnamayanti, Ni Putu Ita; Hartiati, Amna; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September)
This study aims to determine the factors that influence consumer purchase decisions satay fish and determine variables representing each dominant factor in influencing the purchasing decision in Lesehan Warung Merta Sari, Pesinggahan, Klungkung. Data collection techniques in this study conducted by distributing questionnaires to 150  respondents. Data were analyzed using factor analysis method. The results obtained showed that the number of factors that are formed there are 5 factors. First factor were formed by seven variables with eigenvalue of 6.718. Second factor were formed by six variable with eigenvalue of 4.706. Third factor were formed by five variables with eigenvalue of 3.832. Fourth factor were formed of four variables with eigenvalue of 3.285. Fifth factor were formed of two variableswith eigenvalue of 1.639. Keywords: factor analysis, marketing, purchasing decisions of consumers, sate lilit
Keywords: 109,